Processing of mixed fruit juice from mango, orange and pineapple - Begum, Sajeda; Das, Pabitra Chandra; Karmoker, Poly (Fundamental and Applied Agriculture, 2018)
The study was conducted to prepare mixed fruit juice by using mango, pineapple and orange juices. Fully ripen raw mango, pineapple and orange were processed into pulp/juice forms which were analyzed for their composition and consequently processed into mixed fruit juices with a combination of different percentage of mango pulp, pineapple and orange juice. Chemical composition, keeping quality, shelf life and consumers’ acceptability of the products were investigated. Chemical analysis showed that TSS, acidity were increased slightly whereas vitamin C and pH were decreased gradually during the storage periods. Storage studies were carried out up to one month with an interval of one week and the result showed that all the samples were in good condition after one month, though little bit of faded color was found at the end of storage periods. Sample with 35% mango juice, 40% orange juice and 25% pineapple secured the highest score on sensory evaluation and showed the best consumer acceptance. This research reveals that perish- able fruits can be converted to attractive mixed juice and thus increase the shelf-life, which increase value of the product.